2015
DOI: 10.4103/2211-4122.161778
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial longitudinal speckle tracking echocardiography in healthy aging heart

Abstract: Background:Left atrial volume (LAV) and function are connected to the left ventricular (LV) haemodynamic patterns. To define the changes of LAV and functions to counterbalance age-related LV diastolic impairment, this study was undertaken.Methods:2D-Left Atrial Speckle Tracking Echocardiography (2D-LASTE) was used to define both LAV and functions in an aged healthy population (group II) respect to adult healthy controls (group I).Results:Results showed an increasing of left atrial volume indices (LAVI) (maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Still, there is evidence that LV diastolic dysfunction and increased LA volumes are independent predictors of first age-related cardiovascular event in an elderly population [26]. Cacciapuoti et al also confirmed the connection between LA function and volumes and age-related LV dysfunction [23]. With regard to conventional echocardiographic parameters of the LA, numerous studies presented their diagnostic and prognostic role in various clinical scenarios.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Still, there is evidence that LV diastolic dysfunction and increased LA volumes are independent predictors of first age-related cardiovascular event in an elderly population [26]. Cacciapuoti et al also confirmed the connection between LA function and volumes and age-related LV dysfunction [23]. With regard to conventional echocardiographic parameters of the LA, numerous studies presented their diagnostic and prognostic role in various clinical scenarios.…”
Section: Discussionmentioning
confidence: 98%
“…LV diastolic function normally deteriorates with age [23][24][25]. Still, there is evidence that LV diastolic dysfunction and increased LA volumes are independent predictors of first age-related cardiovascular event in an elderly population [26].…”
Section: Discussionmentioning
confidence: 99%